DEVELOPING THE INDONESIAN MASTER STUDENTS RESEARCH MINDSET WITH THE RESEARCH SKILL DEVELOPMENT FRAMEWORK - Yayan Rahtikawati; Dadan Rusmana; Agus Mursidi; AnggunAngkasa Bela Persada; Heri Kurnia (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This qualitative research will identify the core value to prepare Indonesian master students’ research mindset with the Research Skill Development (RSD) framework. The success of learning in the postgraduate program depends on the ability to work with higher research competencies capability. To understand this assumption, we have done a series of data collection, including literature review, unstructured interviews, documentation, and observation. Furthermore, we analyzed the data with a descriptive method to find answers to this study’s questions on the principles of validity and reliability. Our data search process is carried out on secondary data. These, namely, various international scientific journals, discuss the effectiveness and usefulness of the RSD framework in multiple contexts, and understand research experts as a learning tool at postgraduate both at home and abroad. We have done useful searches, for example, with the help of keyword searches such as "Indonesia Master students," "Research Students Mindset", "Research skill development frameworks", and "Preparing students with a Research skills mindset". As a result, we can report that Indonesian students’ research mindset has not yet been honed and developed; it is because the autonomy of learning has not been fully accustomed. In other words, students still do not depend on the lecture system face to face instead of screen to screen. Thus, it is hoped that these results will be the initial stage to prepare Indonesian students with research strength, especially students with postgraduate degrees where research is a core component for success.